2015
DOI: 10.5901/mjss.2015.v6n4s1p193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Media on Researchers’ Academic Performance through Collaborative Learning in Malaysian Higher Education

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 44 publications
4
30
1
1
Order By: Relevance
“…The participants also indicated that they would use social media to improve their research skills and to build relationships with their supervisors thus further improving their academic performance while facilitating academic activities and cooperating with other researchers. As a result of these findings, hypotheses H3b, H3c, H4a, H4b and H5 are confirmed, which agrees with the results of several past studies (Ainin et al, 2015;Alrahmi et al, 2015a;Al-rahmi et al, 2014;Alloway and Alloway, 2012;Al-rahmi et al, 2015b;Al-rahmi et al, 2015c) but contradicts the findings of past studies that suggested that the frequent use of social media harms academic performance (Kirschner et al, 2010).…”
Section: Figure 2 Results For Proposed Frameworksupporting
confidence: 86%
See 1 more Smart Citation
“…The participants also indicated that they would use social media to improve their research skills and to build relationships with their supervisors thus further improving their academic performance while facilitating academic activities and cooperating with other researchers. As a result of these findings, hypotheses H3b, H3c, H4a, H4b and H5 are confirmed, which agrees with the results of several past studies (Ainin et al, 2015;Alrahmi et al, 2015a;Al-rahmi et al, 2014;Alloway and Alloway, 2012;Al-rahmi et al, 2015b;Al-rahmi et al, 2015c) but contradicts the findings of past studies that suggested that the frequent use of social media harms academic performance (Kirschner et al, 2010).…”
Section: Figure 2 Results For Proposed Frameworksupporting
confidence: 86%
“…Using social media to interact with supervisors resulted in a moderate level of satisfaction as social media provided a tool for collaborative learning that improved communication between supervisors as respondents allowing information to be more easily exchanged. Overall, the majority of participants in this study indicated that they would social media for collaborative learning and engagement thus further supporting hypotheses H1a, H1b, H2a, H2b and H3a and the results of previous studies (Al-rahmi et al,2015;Al-rahmi et al,2014;Yu et al,2010;Al-rahmi et al, 2015c). However, these results contradicted the findings of Junco and Cotton (2012) and Madge et al (2009).…”
Section: Figure 2 Results For Proposed Frameworksupporting
confidence: 81%
“…This is done under the assumption that the overall detection accuracy could be enhanced as the gender-specific language structures are collected. This contrasts with previous studies [10], [11] where social media is used for engagement among students. See figure 1.…”
Section: Introductioncontrasting
confidence: 78%
“…However, others highlighted that they use this technology for communication, learning, knowledge management and interactive journalism. Recently, several studies in the developed countries have focused on the enhancement of teaching and learning via social media [16,17,18]. The main aim of this research is to examine the intentions of teachers towards the use of social media as to enhance their teaching and learning activities.…”
Section: Introductionmentioning
confidence: 99%